Review on Financial Analysis - N.B.C.Sidhu , A.Vamshidhar Reddy, Dr.I.Satyanarayana, (International Journal of Scientific Research and Management (IJSRM), 2015)
Analysis refers to the process of critical examination of the financial information contained in the financial statement in order to understand and make decisions regarding the operations of the firm. The analysis is basically study of the relationship among various financial facts and figure as given in a set of financial statements. Complex figures as given in this statements are dissected broken up into simple and variable elements and significant Relationship are established between the elements of thesame statements are different financial statements. This process of dissection, establishing and identifying the financial weaknesses and strengths of the firm. It is indicative of two aspects of a firm i.e. the profitability and the financial position and it are what are known as the objectives of the analysis. Financial management involves managerial activities concerned with the procurement and utilization of funds for business purpose the finance function does with procurement of money taking in to consideration of today’s as well as future need and its effective utilization. Since finance is required to purchase of machinery and raw materials, to pay salaries and wages also for day-to-day expenses.